The Influence of Organizational Communication, Information Technology and Motivation on Employee Performance: Job Satisfaction as an Intervening Variable - Aima, M. Havidz; Zefriyenni, Zefriyenni; Rinaldi, Denny (UPI YPTK Journal of Business and Economics, 2024)
An organization can manage human resources that have performance in accordance with the goals of the organization, Low employee performance affects the image of the organization. The data analysis method uses a probability test of all population elements with a sample of 100 individuals. The study uses Structural Equation Modeling (SEM) and uses SmartPLS. For hypothesis testing, the Path Coefficient is used which aims to measure the direct effect, while the Indirect Effect is used to assess the indirect effect. Based on the results of the study, it explains that organizational communication does not affect employee performance, organizational communication does not affect job satisfaction, information technology does not affect employee performance, information technology does not affect job satisfaction, motivation affects Employee Performance, motivation affects job satisfaction, job satisfaction affects employee performance, job satisfaction does not mediate organizational communication on employee performance, job satisfaction does not mediate information technology on employee performance and job satisfaction is able to mediate motivation on employee performance at the Solok City Health Office.